Word-building ability of historical roots - Doszhan Р.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
This article is considered the definitions of derivative words spreading from one basic cognate word of ancient Turkic origin. Determining a number of words spreading from ancient radical, it can determine the high degree of their word-forming abilities. In addition, such studies undoubtedly make it possible to discover the etymology of the radical and to determine the basic cognate words. Many of the words that are now rooted in the meaning of one another are far removed from each other in meaningful development. It is difficult to find common ground for their comparisons, but only on the basis of sound variants and meaningful comparisons in related languages can only make the right scientific forecasts. In the article the etymology of several word roots is revealed and scientific prognosis is generated by the many words associated with it